Choroidal pericytes promote subretinal fibrosis after experimental photocoagulation - Xueting Luo; Shiqi Yang; Jian Liang; Yuanqi Zhai; Mengxi Shen; Junran Sun; Yiji Feng; Xinmin Lu; Hong Zhu; Fenghua Wang; Xiaodong Sun (The Company of Biologists, 2018)
Subretinal fibrosis results in local destruction of retinal structures and permanent vision loss, representing the end stage of neovascular age-related macular degeneration (AMD). Histological examination of fibrotic specimens from AMD patients has uncovered a wide range of cellular and acellular components. However, their origins and roles in fibrosis remain largely unexplored. Using a laser-induced photocoagulation model with collagen 1α1-GFP reporter mice, we demonstrate, by cell-lineage tracing, that pericytes associating with choroidal microvasculature are activated upon injury and infiltrate into the subretinal space as significant components of fibrotic lesions. In contrast to their choroidal precursors, infiltrating pericytes acquire stellate-like structures, upregulate expression of fibrogenic molecules and colocalize with extracellular fibrotic scar. Collectively, our results identify the choroidal perivascular niche as a novel source of subretinal fibrosis after photocoagulation, and suggest that collagen 1-expressing pericytes are potential targets for therapeutic intervention to suppress subretinal fibrosis and preserve vision.